Unusual 99mTc-pyrophosphate accumulation in aortic aneurysm detected by bone scintigraphy - S. P. Mironov; D. N. Shul’gin; V. V. Malakhov (Вестник рентгенологии и радиологии, 2016)
A clinical observation of focal accumulation of 99mTcpyrophosphate in aortic aneurysm, simulating skeletal pathology of the lumbar vertebra in planar scintigraphy mode, is presented. Additional single-photon emission computed tomography combined with computed tomography-something view allowed to confirm that the radiotracer uptake focus was localized in the distal part of the aneurysm, in the zone of lumen subocclusion by a calcified thrombus. It is suggested that the local tracer accumulation is not only due to calcification but also due to inflammatory, a factor that plays a role in the genesis of an aortic aneurysm